Some Aspects of Memory and History in Recent Native American Fiction: Sherman Alexie's _Flight_ - Šesnić, Jelena (Array, 2010)
For some time now in the humanities there has been a pronounced interest in the way history and memory are intertwined. Sherman Alexie's, and by extension contemporary US ethnic fiction offers surprising and productive, even though fictional and constructed, ways to reconsider this relationship. In terms of some concepts and procedures borrowed from the studies of trauma, the analysis will go to show how trauma incites memory, how this memory in turn is activated in specific, historically contingent lieux de mémoire (P. Nora) essential for Native American culture in the States, and, furthermore, how they occasion the production of ethnic history as an integral part of the national historical narrative. The reading will principally encompass Sherman Alexie's most recent novel "Flight" (2007).